2022
DOI: 10.1021/acsaem.2c01663
|View full text |Cite
|
Sign up to set email alerts
|

Loosening CO Limit 25-Fold for Hydrogen: Coupling Material Development and Operation Optimization of Proton-Exchange Membrane Fuel Cells

Abstract: Assurance of high-quality hydrogen is critical for end usage in proton-exchange membrane (PEM) fuel cell (PEMFC) electric vehicles with a long lifetime and low cost as a trace amount of CO impurities in hydrogen significantly affects the durability and fuel expense. Herein, we demonstrate an effective strategy to reduce the total ownership cost of PEMFC vehicles by coupling material development and operation optimization, aiming to obtain the optimal tolerance limit for hydrogen impurities. An electrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…To further investigate the difference in resistance to S 2− poisoning between PtRu/C and Pt/C, the physical and chemical characteristics of both catalysts were compared to reveal the relation between the electronic structure and affinity of S 2− to Pt sites. Figure 8 displays the XPS spectra for the two catalysts before and after 50 μM S 2− poisoning for 1 h. Notably, the binding energy of the Pt 4f peak in PtRu/C is shifted positively by 0.4 eV in comparison to Pt/C, suggesting a modification in the Pt electronic structure caused by Ru alloying 16 (Figure 8a). The introduction of Ru atoms into the Pt lattice was reported to induce the strain and ligand effects that involve the lattice change in metal and the modification of the Pt electronic structure, respectively, resulting in the change in the Pt d-band center to move toward or away from the Fermi level.…”
Section: Electronic Structure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the difference in resistance to S 2− poisoning between PtRu/C and Pt/C, the physical and chemical characteristics of both catalysts were compared to reveal the relation between the electronic structure and affinity of S 2− to Pt sites. Figure 8 displays the XPS spectra for the two catalysts before and after 50 μM S 2− poisoning for 1 h. Notably, the binding energy of the Pt 4f peak in PtRu/C is shifted positively by 0.4 eV in comparison to Pt/C, suggesting a modification in the Pt electronic structure caused by Ru alloying 16 (Figure 8a). The introduction of Ru atoms into the Pt lattice was reported to induce the strain and ligand effects that involve the lattice change in metal and the modification of the Pt electronic structure, respectively, resulting in the change in the Pt d-band center to move toward or away from the Fermi level.…”
Section: Electronic Structure Analysismentioning
confidence: 99%
“…Among these impurities, H 2 S and CO are regarded as the key poisons that severely affect the durability of the carbon-supported Pt (Pt/C) catalyst for the PEMFC anode. For CO poisoning, extensive investigations have been performed on the mechanism exploration of the CO harmful effect on PEMFCs and also the development of mitigation strategies (e.g., oxygen bleeding, electrochemical oxidation, and employment of alternative catalysts [e.g., platinum (Pt)-ruthenium (Ru)/C)]). However, for H 2 S impurity, several literature studies have been conducted on its detrimental effect on PEMFCs, which showed that trace H 2 S can be strongly absorbed on Pt reactive sites and it is easier to severely poison the Pt/C catalyst. The poisoning of Pt/C by H 2 S impurity results in a significant decrease in available Pt reactive sites for anode hydrogen oxidation reaction (HOR) catalysis, which ultimately affects the output performance and durability of PEMFCs.…”
Section: Introductionmentioning
confidence: 99%